A CFD Simulation for an Air Breathing PEMFC for Power Source Portable Applications. (14th September 2015) - Carcadea, Elena; Varlam, Mihai; Stefanescu, Ioan; Ingham, Derek; Marinoiu, Adriana; Patularu, Laurentiu; Raceanu, Mircea; Schitea, Dorin
Abstract : This paper presents a numerical investigation for a 44 cm 2 air breathing PEM fuel cell. We analyzed the influence of some operating and design parameters on the cell performance. The numerical solution based on ANSYS Multiphysics software and Fuel Cell Module offered an optimal performance at a cell with the cathode channel dimensions of 1.5 mm x 1.5 mm. Analyzing the polarization curves it can be noticed that for operating voltages greater than 0.75V, the channel width and depth has only a small influence on the performance, while at lower operating voltages the influence of the channels size on the performance become significant. In identifying the critical parameters and for having an insight into physical mechanisms that can influence the fuel cell we analyzed the water mass fraction and membrane protonic conductivity distributions, the relative humidity and temperature in the anode and the pressure and temperature in the cathode side.